'A higher degree of scholarship': Pagans and the language of scholarly authority. Issue 1 (2nd January 2016) - Buccitelli, Anthony Bak
Abstract: Through an exploration of the intellectual history and contemporary writings of the Pagan movement, this study will examine the lineage of 'knowledge-based' authority in contemporary Paganism. In particular, it will illuminate how the intellectual lineage of Pagan writings helped contemporary writers respond to a moment of crisis in Paganism, and it will provide an explanation for the traditionalised use of the rhetorical modes of scholarly authority among Pagan writers.